Revitalization of the Character Values of Pencak Silat Pagar Nusa and Its Relevance to Social Studies Learning - Rony Adi Saputro; Ali Imron; Sugiantoro; Dhimas Bagus Virgiawan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This research aims to analyze the character values that develop in Pencak Silat Pagar Nusa activities and its revitalization strategies in supporting social studies learning. The research uses a descriptive qualitative approach with the research location at Padepokan Pencak Silat Pagar Nusa, Ngluyu District, Nganjuk Regency. Data were obtained through observation, interviews, and documentation, then analyzed using the Miles and Huberman model with validity tests through triangulation techniques. The results of the study show that the character values that develop include religious, discipline, responsibility, honesty, tolerance and social concern, as well as hard work and never giving up. Revitalization of character values is carried out through example, habituation, giving advice, enforcing organizational rules, and strengthening solidarity between members. These values have a strong relevance to social studies learning, especially in socialization and personality formation materials, so that they can be used as contextual learning resources based on local wisdom that support the strengthening of students' character.